Anatomopathology of the Superstructure of the Stapes in Patients with Otosclerosis - Carvalho,Bettina (2015)
Introduction Otosclerosis is a disease that causes bone resorption and deposition in the auditory structures, leading to deafness. Many studies have evaluated the histopathology of the stapes footplate in this disease (osteoblasts, osteoclasts, vascular proliferation, fibroblasts, and histiocytes), but we found no studies in the literature involving the histology of the superstructure of the stapes. Objectives To perform an analysis under optical microscopy of histopathologic findings of the superstructure of the stapes from patients with otosclerosis. Methods A contemporary cross-sectional cohort study of pathology analysis of superstructures of the stapes of patients with otosclerosis. Results Fifteen superstructures of stapes in patients with otosclerosis operated in our service and four stapes of cadavers used for dissection (controls) were evaluated. No areas of bone resorption or deposition or presence of osteoclasts and osteoblasts in the superstructure of the stapes were found. However, we found in themore distal portions of the crura areas with prominent cementitious lines and woven bone, which was different than the mature trabecular bone found in the head of the stapes or in the controls. Conclusion There were histologic changes in the superstructure of the stapes in patients with otosclerosis operated in our service.